2012
DOI: 10.3945/jn.112.163204
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Reduces Hyperglycemia and Increases Satiety Hormone Secretion More Effectively When Used with a Novel Polysaccharide in Obese Zucker Rats3

Abstract: The novel polysaccharide (NPS) PolyGlycopleX (PGX) has been shown to reduce glycemia. Pharmacological treatment with sitagliptin, a dipeptidyl peptidase 4 (DPP4) inhibitor, also reduces glycemia by increasing glucagon-like peptide-1 (GLP-1). Our objective was to determine if using NPS in combination with sitagliptin reduces hyperglycemia in Zucker diabetic fatty (ZDF) rats more so than either treatment alone. Male ZDF rats were randomized to: 1) cellulose/vehicle [control (C)]; 2) NPS (5% wt:wt)/vehicle (NPS);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
3
14
1
Order By: Relevance
“…As mentioned earlier, GLP-1 secretion can also be stimulated by metabolites produced by the gut microbiota [25]. Reimer et al demonstrated that co-administration of sitagliptin and a viscous fermentable fibre, which is broken down into SCFA, more effectively reduced fasting glycaemia in obese Zucker rats than either treatment alone [53]. Similar results were obtained in the same model when this fibre was combined with metformin or with metformin and sitagliptin [54].…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiasupporting
confidence: 75%
“…As mentioned earlier, GLP-1 secretion can also be stimulated by metabolites produced by the gut microbiota [25]. Reimer et al demonstrated that co-administration of sitagliptin and a viscous fermentable fibre, which is broken down into SCFA, more effectively reduced fasting glycaemia in obese Zucker rats than either treatment alone [53]. Similar results were obtained in the same model when this fibre was combined with metformin or with metformin and sitagliptin [54].…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiasupporting
confidence: 75%
“…PolyGlycopleX (a-D-glucurono-a-D-manno-b-D-manno-b-D-gluco), (a-L-gulurono-b-D mannurono), b-D-gluco-b-D-mannan (PGX) is a highly viscous and fermentable functional fiber that has been shown to reduce hyperglycemia and increase GLP1 secretion in obese Zucker rats (Grover et al 2011b). We have recently demonstrated that the individual glycemialowering potential of sitagliptin and PGX can be augmented when they are co-administered in obese Zucker rats (Reimer et al 2012a). Whether the effectiveness of MET and sitagliptin/metformin (S/MET) can likewise be improved with co-administration with PGX is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The drugs were administered for 6 weeks. The dose of PGX has been shown to reduce HbA1c and serum cholesterol and increase b-cell mass previously (Grover et al 2011b, Reimer et al 2012a. Doses of MET and sitagliptin were selected from the low end of the ranges used in the literature (Chen et al 2011, Maiztegui et al 2011, Pyra et al 2012 in order that potential synergistic effects with PGX could be detected.…”
Section: Rats and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations